2017
DOI: 10.23736/s0391-1977.16.02567-0
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal hormones, gut microbiota and non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the hepatic manifestation of the metabolic syndrome and has a complex pathophysiology with multiple pathways of development and progression implicated. Intestinal hormones regulate multiple biological functions and may play a role in the pathogenesis of non alcoholic fatty liver disease (NAFLD) by affecting food intake, body weight and insulin resistance. Bacterial products can affect the secretion of these hormones and thus have an effect on metabolism. Gut microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 65 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…With CC-SKO treatment, the relative abundance of Proteobacteria increased to close to that of the Control group. A study showed that fat feeding could promote certain gut bacteria such as Lactobacillus [21]. The results of this experiment showed that the structure of the liver tissue in the CCSKO group was similar to that in normal control group, and the structure was intact without degeneration and necrosis.…”
Section: Discussionmentioning
confidence: 64%
“…With CC-SKO treatment, the relative abundance of Proteobacteria increased to close to that of the Control group. A study showed that fat feeding could promote certain gut bacteria such as Lactobacillus [21]. The results of this experiment showed that the structure of the liver tissue in the CCSKO group was similar to that in normal control group, and the structure was intact without degeneration and necrosis.…”
Section: Discussionmentioning
confidence: 64%
“…The gut microbiota participates in intestinal energy metabolism, and their implication in the pathogenesis of obesity and MASLD is being increasingly recognized. Similarly, intestinal hormone pathways are potential therapeutic targets for the management of MASLD [ 151 ]. Newly identified targeted drugs like PPAR agonists, FXR agonists, and THR-β agonists are currently being investigated in clinical trials and are anticipated to be applied for the treatment of MASLD.…”
Section: Research Prospects For Therapeutic Strategiesmentioning
confidence: 99%
“…Extrahepatic inflammatory factors can contribute to the onset and progression of NAFLD, such as adipokines [21] and gut hormones [22]. For example, pro-inflammatory cytokines secreted from adipose tissues and intestinal epithelium cells, such as IL-1β and tumor necrosis factor (TNF)-α can transfer into the liver to induce immune cell activation [23,24].…”
Section: Metabolic Diseases-associated Extrahepatic Inflammation and ...mentioning
confidence: 99%
“…In addition, adipokines derived from obese tissues (e.g., brown adipose tissues) can be delivered into the liver to cause hepatic inflammation [26]. For example, an increase in circulating leptin levels and a decrease in adiponectin levels are associated with the increased severity of NAFLD [21]. Inflammatory cytokines and chemokines secreted from adipose tissue can impact systemic inflammation, including liver tissues.…”
Section: Obesitymentioning
confidence: 99%
See 1 more Smart Citation